2014
DOI: 10.5296/ijele.v2i2.5868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Facebook Collaborative Writing Groups on ESL Undergraduates’ Writing Performance

Abstract: This study investigated the effects of Facebook collaborative writing groups on ESL undergraduates writing performance. A total of 33 second year ESL students were involved in this study. The students were divided into two groups; control and experimental groups. Facebook, as the treatment in this study was compared to a conventional method; face-to-face in the collaborative writing activities. The comparison between face-to-face and Facebook collaborative writing groups were made in order to measure students'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Therefore, the second hypothesis was accepted. This result agrees with the results of some studies which found that CBCW yielded the production of better quality texts (e.g., Abrams, 2019;Al-Shumaimeri, 2011;Arslan & Sahin-Kizil, 2010;Bailey & Judd, 2018;Beltrán, 2010;Daskalogiannaki, 2012;Dobao, 2012;Doult & Walker, 2014;Kessler & Bikowski, 2010;Mak & Coniam, 2008;McDonough & García-Fuentes, 2015;Mills & Exley, 2014;Myers, 2014;Shukor & Noordin, 2014;Strobl, 2014;Togatorop, 2015;Villarreal & Gil-Sarratea, 2019;Wichadee, 2011;Yeh, 2014;.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, the second hypothesis was accepted. This result agrees with the results of some studies which found that CBCW yielded the production of better quality texts (e.g., Abrams, 2019;Al-Shumaimeri, 2011;Arslan & Sahin-Kizil, 2010;Bailey & Judd, 2018;Beltrán, 2010;Daskalogiannaki, 2012;Dobao, 2012;Doult & Walker, 2014;Kessler & Bikowski, 2010;Mak & Coniam, 2008;McDonough & García-Fuentes, 2015;Mills & Exley, 2014;Myers, 2014;Shukor & Noordin, 2014;Strobl, 2014;Togatorop, 2015;Villarreal & Gil-Sarratea, 2019;Wichadee, 2011;Yeh, 2014;.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies found a positive effect for CBCW on writing quantity (e.g., Daskalogiannaki, 2012;Doult & Walker, 2014;Mak & Coniam, 2008;Mills & Exley, 2014;Myers, 2014;Storch, 2011;Yim, Wang, Olson, Vu, & Warschauer, 2017) and quality (e.g., Abrams, 2019;Al-Shumaimeri, 2011;Arslan & Sahin-Kizil, 2010;Bailey & Judd, 2018;Beltrán, 2010;Daskalogiannaki, 2012;Dobao, 2012;Doult & Walker, 2014;Kessler & Bikowski, 2010;Mak & Coniam, 2008;McDonough & García-Fuentes, 2015;Myers, 2014;Shukor & Noordin, 2014;Strobl, 2014;Togatorop, 2015;Villarreal & Gil-Sarratea, 2019;Wichadee, 2011;Yeh, 2014;. Therefore, the researcher decided to investigate the effect of CBCW on both the quantity and quality of EFL students' writing.…”
Section: Cbcw and Writing Quantity And Qualitymentioning
confidence: 99%
“…Some researchers have investigated the role of blended learning in ESL/EFL writing skill in terms of its effectiveness (Adas & Bakir, 2013;Keshta & Harb, 2013;Shafiee et al, 2013;Arslan, 2014;Abdulmajid, 2014). Other researchers had also examined the effectiveness of using collaborative learning in improving writing (Al-Ahmad, 2003;Taki & Fardafshari, 2012;Jafari & Ansari, 2012;Grami, 2012;Shukor & Noordin, 2014). Results of these studies revealed that blended learning and collaborative learning have been effective in improving students' WP.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, a number of studies have shown how English lessons have taken advantage of learners' communication in the Internet environment. Instructors have capitalized on students' enthusiasm for interacting (either one-on-one or in a group chat) on Facebook and their familiarity with Facebook functions that can serve educational purposes (e.g., Annamalai, Tan, Abdullah, & Sivagurunathan, 2015;Annamalai, Tan, & Abdullah, 2016;Promnitz-Hayashi, 2011;Razak & Saeed, 2014;Reid, 2011;Shih, 2011;Shukor & Noordin, 2014). Online discussion forums have also been employed as a pedagogical tool (e.g., Bassani, 2011;Miyazoe & Anderson, 2010;Tan, 2017;Wang & Yang, 2012).…”
Section: Resultsmentioning
confidence: 99%